ChemInform Abstract: Arene‐Ruthenium(II) Complexes with Hydrophilic P‐Donor Ligands: Versatile Catalysts in Aqueous Media. Issue 40 (30th September 2014) - Crochet, Pascale; Cadierno, Victorio
Abstract Review: 151 refs.